PROSES PENGAMBILAN KEPUTUSAN DALAM KELUARGA UNTUK TETAP BERTAHAN TINGGAL DI PERMUKIMAN RAWAN BANJIR - Rizza Armelvia Sari; Retno Wahyuningtyas; Permata Jali Dimasiosz (Jurnal Pendidikan Sosiologi Undiksha, 2025)
This research was motivated by the recurring issue of flooding in residential areas of Lubuk Buaya Subdistrict. The study aims to describe the decision-making process within families in choosing to remain in flood-prone settlements and to identify the factors that influence such decisions. The theoretical framework employed is the rational choice theory proposed by James S. Coleman. The findings reveal that the decision-making process within families to stay in flood-prone areas occurs in two ways: through individual decisions made by each spouse, and through collective decisions made by all family members based on mutual agreement. Several factors influence the family's decision to remain in these areas, including length of residence, social relationships, proximity to workplace, and housing status